2008
DOI: 10.2116/analsci.24.321
|View full text |Cite
|
Sign up to set email alerts
|

Poly(methylmethacrylate) Microchip Electrophoresis of Proteins Using Linear-poly(acrylamide) Solutions as Separation Matrix

Abstract: Poly(methylmethacrylate) (PMMA) microchip electrophoresis of sodium dodecyl sulfate-protein complexes (SDS-PC) using linear-poly(acrylamide) (L-PA) as a separation matrix was investigated. Prior to electrophoresis, channel walls of PMMA were modified with methylcellulose (MC) to prevent adsorption between channel walls and SDS-PC. Size-based protein separation (SBPS) was successfully performed using the MC-coated microchips with Ferguson plot-fittings. The entangled L-PA solution provided high resolution of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Even though the suppression in EOF has been achieved in the literature, the absolute value of EOF mobility and the degree of suppression have not been reported. Protein separation in PDMA gels has been performed in a PMMA microchip, using a variety of methyl cellulose (MC) compounds as EOF suppressor . In these studies, the concentration of MC was varied from 0.01 to 1% (w/v).…”
Section: Resultsmentioning
confidence: 99%
“…Even though the suppression in EOF has been achieved in the literature, the absolute value of EOF mobility and the degree of suppression have not been reported. Protein separation in PDMA gels has been performed in a PMMA microchip, using a variety of methyl cellulose (MC) compounds as EOF suppressor . In these studies, the concentration of MC was varied from 0.01 to 1% (w/v).…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of two closely related bacteriophages, T2 and T4, showed that this technique was sufficiently sensitive and gave high enough resolution between protein peaks to distinguish these two phages. Baba's group investigated various polymer solutions such as linear‐polyacrylamide 135, and dextran 67 as potential low‐viscosity protein sieving matrices. Reproducible, highly efficient size‐based separation of proteins was successfully achieved with a coated microchip reducing EOF and protein adsorption.…”
Section: Separation Modes For Protein Electrophoresis On Microchipsmentioning
confidence: 99%
“…The lifetimes of these columns were limited (usually less than 10 runs) [12], and the run-to-run reproducibility was poor. Currently, replaceable and water-soluble linear or slightly branched polymers, such as linear polyacrylamide [1113], poly(ethylene glycol) [11], poly(ethylene oxide) [14], dextran [1517], pullulan [18, 19] and cross-linked polyacrylamide [2022] are used as sieving matrices for CGE [5, 11, 2325]. Availability of these polymer matrices has led to improved reproducibility and robustness of this methodology.…”
Section: Introductionmentioning
confidence: 99%